EFEKTIVITAS PROGRAM TRAINING TERHADAP TINGKAT KUALITAS KERJA KARYAWAN DI DEPARTEMEN FRONT OFFICE HOTEL GRAND DAFAM ROHAN JOGJAKARTA - Nur Widya Asiska Pratiwi; Agus Solikhin; Kris Cahyani Ermawati (Sekolah Tinggi Pariwisata Sahid Surakarta, 2020)
The objectives of this study were (1) To determine the effectiveness of the training program at the Front Office Hotel Grand Dafam Rohan Jogja. (2) To find out what are the effects of the effectiveness of the training program on the level of work quality of employees at the Grand Dafam Rohan Jogja hotel. Hotels as a type of accommodation that are often used by tourists are growing rapidly in Indonesia. The more complete facilities that support guest comfort and the benefits offered by a hotel are expected to attract guests' attention optimally. The method used in this research is descriptive qualitative method. Data collection techniques in this study include observation, interviews, documentation, and literature study. The effectiveness of training is generally seen from the extent to which the training achieves the stated behavioral goals and how much it costs for return training because this effectiveness is a way to benefit the company and affects the level of employee work quality. Based on the results of research and discussion, information can be obtained that the quality of employee work can be seen from the work ability of employees.